Factors in Measuring the Earning Quality in the Consumption Industry of Public Companies - Dedi Putra SE,.M.S.Ak; Pebrina Swissia; Mutiara Dwi Firdiana (Proceeding International Conference on Information Technology and Business, 2021)
The purpose of this study was to empirically find the effect of reporting timeliness, default risk, and the audit committee on earnings quality in consumer goods industrial sector companies listed on the IDX in 2016-2019. The data in this study used secondary data in the form of annual financial reports and annual reports for 2016-2019. The method of data collection used the purposive sampling technique. The population in this study was the consumer goods industry sector companies listed on the IDX in 2016-2019. The number of samples was 21 companies. The data analysis technique used the multiple linear regression analysis with SPSS software version 22. The result of this study found that the timeliness of reporting and the audit committee variables had no significant effect on earnings quality. Meanwhile, the default risk had a significant effect on the earnings quality.Keywords- Earnings quality, Timeliness of Reporting, Default Risk, Audit Committee